Repositioning Chromones for Early Anti-inflammatory Treatment of COVID-19 - Sestili, Piero; Stocchi, Vilberto (Frontiers in Pharmacology, 2020)
The COVID-19 pandemic is posing an unprecedented sanitary threat. In the absence of specific vaccines and anti-SARS-CoV-2 drugs, medicines that may assist in tackling the emergency and limiting the high number of fatalities are urgently needed. The repositioning of available drugs to treat COVID-19 is the only and rapid option in the face of the lack of direct antiviral agents and vaccines available. In this light it is important to focus on available drugs, which, based on their pharmacodynamics, could plausibly attenuate viral growth as well as COVID-19’s worst complications. This is the case of chloroquine and tocilizumab which seem to limit virus replication and the severity of interstitial pneumonia, respectively. However, these treatments, particularly those aimed at containing inflammation, are still reserved for the most severe cases. This commentary elaborates on the pharmacological rationale of repositioning the mast cell stabilizer chromones as an adjunctive treatment for SARS‐CoV‐2 infection, and proposes their practical clinical testing as an early, safe, and cost-effective anti-inflammatory intervention in COVID-19 to limit the eventual secondary progression toward life-threatening respiratory complications.